Armed Soviet and Party Activists and Other Paramilitary Units - Starkauskas, Juozas (Genocidas ir rezistencija, 1999)
In the second half of 1945, the occupiers, convinced that it would be difficult to break the resistance of our people with harsh military force, began to implement the directive of 12 October 1945 issued by the People’s Commissar of the NKVD, Lavrentiy Beria. The directive ordered the coordination of military force with agency–type measures, i.e., they began to create a wide network of agents-informants. In addition to agents, it was necessary to expand the ranks of people openly supporting the Soviet government. Efforts were made to arm not only members of the Communist Party and the Komsomol, i.e., those people who recklessly linked their fate to the occupiers, but also a significant number of civil servants.